Suspension system design for pedal-assisted cargo E-quadricycle - Genç, Mehmet Onur (Murat CİNİVİZ, 2024)
Electro Micro-Mobility (EMM) has widely increased in Today‘s transportation preferences. The suspension system design based on the road profile in E-Quadricycle needs further investigation to present more optimized EMM vehicles soon. In this study, the pedal-assisted Cargo E-Quadricycle is investigated based on powertrain system modeling considering suspension system design. System modeling is applied to have an optimized suspension system design specified for Cargo E-Quadricycle to provide more comfortable driving. To achieve these targets, one-dimensional physical modeling is obtained, and the key parameters for system design are defined based on the State-space system modeling definition. In the next phase, the suspension system is constructed as a passive-controlled type with assigned suspension parameters considering natural frequency to provide driving comfort in urban transportation. Because four-wheeler Pedal-Assisted Cargo E-Quadricycles have specific vehicle kinematics and dynamics based on their own limited acceleration system and vehicle design, this study presents the suspension system design steps and remarkable dynamic concerns.
2220390
Keywords: Mechanical Engineering; Makine Mühendisliği